Modeling volumes of agricultural production: data of Russian regions in 2017 and 2018 (Dimensión Empresarial, 2022)
The study was based on the development of production functions that characterize the activities of agricultural enterprises in the regions of Russia. Official statistical information on 65 regions of Russia for 2017 and 2018 was used. The conducted research made it possible to identify factors (investments in fixed assets, wages of employees, and ratio of crop production to livestock production) that affect the volume of production in the agricultural sector in the regions of Russia and suggest using three-factor production functions of high quality to describe this influence. It is proved that the economy of the country's regions has not reached saturation with agricultural products and there are significant reserves for further development of this sector. The developed production functions are effective management tools that allow assessing the level of use of financial and labor resources.
Keywords: Production function; agriculture; investments in fixed assets; wages; regions of Russia